Xanthene-based polarity-sensitive fluorescent probe with large Stokes shifts for simultaneous two-color visualizing of lipid droplets and lysosomes. (December 2022) - Hu, Qingfei; Zhang, Haitao; Ye, Peng; Ma, Shanghong; Zhu, Xiuzhong; Bai, Yang
Abstract: Lipid droplets (LDs) and lysosomes interact as important intracellular subcellular organelles in many physiological and pathological processes. Two-color imaging fluorescent probes have become an important tool for studying the interaction between lipid droplets and lysosomes in cells. Based on the variance in polarity between LDs and lysosomes, a polarity-sensitive probe LD-H-Lyso was designed and synthesized with an xanthene fluorophore as the main body, moreover we introduced a morpholine group into the main structure of the probe to enable it targeting lysosomes. The maximum emission wavelengths of LD-H-Lyso in 1, 4-dioxane, acetone and dimethyl sulfoxide were 549 nm (yellow wavelength range), 624 nm (red wavelength range) and 661 nm (red wavelength range) respectively under excitation at 405 nm. The maximum redshift of the fluorescence emission was 112 nm and the maximum Stokes shift was 223 nm. Meanwhile, the results of cell imaging showed that LD-H-Lyso was able to visualize both LDs (yellow channel) and lysosomes (red channel) with high specificity, with pearson's correlation coefficient of 0.96 for LDs and 0.97 for lysosomes. Furthermore, staining of HepG2 cells using LD-H-Lyso allowed monitoring a corresponding decrease or increase in the number of LDs that were lit in starved/oleic acid-treated cells, with a weak effect on lysosomes displayed in the red channel. Similarly, chloroquine-treated cells exhibited poorer targeting of the probe to lysosomes compared to normal cells, resulting in reduced lamellar fluorescence in the red channel and less altered fluorescence in the yellow channel. Thus, LD-H-Lyso presented significant potential as a new monitoring tool that can simultaneously label both organelles and enable monitoring of individual organelles to explore the interaction of LDs and lysosomes. Graphical abstract: The polarity-sensitive fluorescent probe LD-H-Lyso enables two-color visualization of lipid droplets and lysosomes. Image 1 Highlights: A novel xanthene derivative, LD-H-Lyso, was synthesized as a fluorescent probe for labeling lipid droplets and lysosomes. LD-H-Lyso is highly sensitive to polarity and has a solvatochromic effect. LD-H-Lyso was successfully applied to cell imaging, enabling simultaneous visualization of lipid droplets and lysosomes in two colors.